2022
DOI: 10.1155/2022/3287117
|View full text |Cite|
|
Sign up to set email alerts
|

Visual Evaluation of Urban Streetscape Design Supported by Multisource Data and Deep Learning

Abstract: This paper integrates classical design theory, multisource urban data, and deep learning to explore an accurate analytical framework in a new data environment, providing a scientific analysis path for the “where” and “how” of greenways in a high-density built environment. The analysis is based on street view data and location service data. Through the integration of multiple data sources such as street scape data, location service data, point-of-interest data, structured web data, and refined built environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…as if the landscape was like a painting [26]. Therefore, landscape designers usually use the visual methods of landscape picture [27] to develop design ideas. However, this approach can sometimes neglect the balance of ecosystem and the involvement of sensory aesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…as if the landscape was like a painting [26]. Therefore, landscape designers usually use the visual methods of landscape picture [27] to develop design ideas. However, this approach can sometimes neglect the balance of ecosystem and the involvement of sensory aesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…It can not only protect the environment and optimize the quality of life, but also has the characteristics of low price, easy acquisition and repeated use [9]. Feng et al (2022) integrated multi-source urban data and deep learning algorithms, taking the urban greenway planning research on both banks of Suzhou River in Shanghai as an example, to study human-oriented urban design planning issues, and provide strong support for human-oriented urban design practice [10]. Pan and Jiang (2022) constructed an evaluation index system for the suitability of urban greenway layout under the background of park city, and obtained the road with the highest suitability score through big data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%